Suspending Voluntary Reserve Service: New Questions in Israeli Military Ethics - Kasher, Asa (Conatus - Journal of Philosophy, 2023)
Military activities with the framework of the IDF [Israel Defense Force] is carried out by citizens in a variety of positions. In addition to the ordinary positions of career officers and NCOs, the IDF consists of conscripted men and women as well as reservists. Some of the latter serve under an ordinary command to serve for a certain relatively short period. Other reservists, including pilots and special forces officers have served since they volunteered to serve. Facing the political clash between the government, who have been viewed as trying to change the democratic nature of the state, and the popular opposition, who have tried to protect the judiciary and other elements of democracy, many officers who belong to the latter reservist group have suspended their voluntary service or even retired. Their decision has raised the obvious issue of whether such decisions can be justified, morally, ethically, and democratically. This is the topic of the present paper.